Real-Time Hidden Data Transmission Using Lora - Satyavathi, D.Monica; Mala, B.Vandana; Vamsi, Ch.Veera; Chiranjeevi, Ch.Chiranjeevi; Neeraj, Ch.Neeraj (International Journal of Advanced Science Computing and Engineering, 2022)
Nowadays, it has become a crucial task in transferring confidential data for military departments, many multinational companies, etc.Â  The important requirement is that the data that has been transmitted should not be visible to hackers or third parties from another end. To satisfy this requirement a wireless technology LoRa is used. Long-distance and low-power wireless communication technologies such as LoRa, Sigfox, and Narrowband-Internet of Things (NB-IoT) were developed in recent years. These technologies can contribute to indoor and outdoor smart applications with minimal power consumption. In this study, the LoRa wireless communication technique was used as the primary data communication method, enabling the device to communicate without requiring an Internet connection or a SIM card. This technology can be implemented in military and defense areas.